Creative and Innovative Entrepreneurial Spirit for Students of the Bina Amanah Cordova Entrepreneurship School - Deasy Aseanty; Khomsiyah; Lucy Warsindah; Shafrani Dizar (Jurnal Pengabdian Masyarakat Bestari, 2023)
The success of a business depends on the success of the entrepreneur in running it. Basicly every human being has a nature in the form of talent that is in him. One of the ways to become a successful entrepreneur is self-management, knowing one's own potential and skills, managing talent well. This needs to be accompanied by creativity that produces brilliant ideas to make a business change towards improvement. Business development by relying on creativity in an entrepreneur, this will bring up an innovation. Creativity and innovation are 2 (two) things that are very related; which is not possible in humans all of a sudden. Starting with equipping and training students to be more creative and innovative. If they have entered as entrepreneurs, they are also required to strive to increase creativity and innovation so that the business they are running can develop and be sustainable.